Determinan Indeks Pembangunan Manusia di Kabupaten Aceh Tamiang - Sumono Sumono; Nurlina Nurlina; Iskandar Iskandar (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze the influence of Per Capita Income, Poverty Rate, and Unemployment Rate on the Human Development Index (HDI) in Aceh Tamiang Regency. This study utilizes secondary data from the Central Statistics Agency of Aceh Tamiang Regency for the period 2010–2023 and is analyzed using multiple linear regression with Eviews 10 software. The results indicate that the Per Capita Income variable has a negative and significant effect on the HDI. The poverty rate variable has a negative and significant effect, while the unemployment rate variable has a negative but insignificant effect on the HDI in Aceh Tamiang Regency. Therefore, it can be concluded that increasing per capita income and reducing poverty and unemployment rates can drive improvements in the Human Development Index. Therefore, the local government is expected to focus more on policies related to increasing income and reducing poverty and unemployment to accelerate human development in this region.